Recent advances of nanovaccines on cancer theranostics - Yuan, Xiaobing; Xu, Tianyou; Hussain, Mubashir; Liu, Bin; Zhu, Jianwei (Frontiers in Nanotechnology, 2025)
Cancer is a leading cause of death worldwide, with an estimated 20 million new cancer cases and 9.7 million cancer deaths worldwide in 2022. Immunotherapy provides innovative strategies among the most groundbreaking developments in cancer treatment. Cancer vaccines, as a form of immunotherapy, have a great prospect to help patients resistant to other standard-of-care immunotherapies. On the other hand, the various properties of nanomaterials play an essential role in the collecting, maturation, and activation of the immune system. Cancer vaccines based on nanomaterials (also called nanovaccines) can be specifically delivered to target tissues and cells through nanocarriers and nanoplatforms, thereby improving efficacy, extending the duration of antitumor immunity, and minimizing side effects. This paper reviewed the research progress of some nanovaccines in cancer immunotherapy, including polymer nanoparticle vaccine, liposome nanoparticle vaccine, cell-based nanoparticle vaccine, inorganic nanoparticle vaccine, adjuvant and auxiliary work. We believe that polymer nanoparticle-based nanovaccines have the most widespread applications currently, while liposome nanovaccines using mRNA are expected to see greater development in the future. We also think that nanovaccines can play a great role in cancer prevention and treatment, especially in prolonging the life span of patients.